Gabon : Second Review Under the Stand-By Arrangement, Request for Waiver of Performance Criterion, and Review of Financing Assurances. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The staff report for the Second Review Under the Stand-By Arrangement (SBA) on Gabon focuses on economic developments and policies. The program supported by the 14-month SBA aims at promoting non-oil GDP growth, while sustaining fiscal adjustment and improving public expenditure management. All performance criteria for end-September 2004 were observed, even though there were small slippages in the indicative targets for non-oil revenue and the net reduction of unpaid payments orders at the treasury. The macroeconomic environment has improved since the first review, reflecting slightly higher oil production and considerably higher oil prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet